Young Librarians Unite: Possibilities for Professional Transformation in Japanese Librarianship / Eriko Amano - Amano, Eriko (2011)
The interorganizational networking communities have spontaneously emerged among young Japanese librarians in recent years. This study explores the role of the communities from the perspectives of professional knowledge management, social networks and social capital, and the possibilities to reconstruct the Japanese librarianship. The research questions consist of; What outcomes did young librarians who hadparticipated in the interorganizational social networking communities get especially in terms of knowledge acquisition and affections?What possibilities do the young librarians communities have to transform Japanese librarianship? Method –Semi-structured in-depth interviews were conducted with 5 librarians to gain insight into how they engage in and feel about outside social networking activities and training opportunities. Findings –The results showed that the young librarians‘ voluntary communities helped build social networks, provided opportunities for the transfer of tacit knowledge, and was felt to be a source of motivation for the participants. They also suggested that they had possibilities to give a significant impact on the transition of the Japanese librarianship.